2020
DOI: 10.7150/jca.43518
|View full text |Cite
|
Sign up to set email alerts
|

Surgery on primary tumor shows survival benefit in selected stage IV colon cancer patients: A real-world study based on SEER database

Abstract: Objectives: Most patients with stage IV colon cancer did not have the opportunity for curative surgery, only selected patients could benefit from surgery. This study aimed to determine whether surgery on the primary tumor (SPT) should be performed in patients with stage IV colon cancer and how to select patients for SPT. Methods: This study included 48,933 patients with stage IV colon cancer who were identified in the Surveillance, Epidemiology and End Results (SEER) database between 1998 and 2015. Propensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…According to a study, PTR is performed in over 50% of patients with stage IV CRC, and many doctors still prefer routine use of this treatment. This may be because many current studies suggest that PTR can provide significant survival benefits [7,10,12,15,[23][24][25]. In a Canadian study of stage IV CRC patients who underwent chemotherapy between and 2006 to 2010, 199 patients underwent upfront PTR, and 127 patients did not [24].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study, PTR is performed in over 50% of patients with stage IV CRC, and many doctors still prefer routine use of this treatment. This may be because many current studies suggest that PTR can provide significant survival benefits [7,10,12,15,[23][24][25]. In a Canadian study of stage IV CRC patients who underwent chemotherapy between and 2006 to 2010, 199 patients underwent upfront PTR, and 127 patients did not [24].…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Involving the effect of systemic therapy, there are still some studies support that PTS makes overall survival improvement, but they ignore the difference between metastatic sites especially the lung and liver considering the probable better outcome of the former. [8,11,30] In the situation of these contradictions between different system review about PTS in mCRC, we think that may be related with the great heterogeneity between the primary evidence, the large time span between studies and the different use of extra pharmacotherapy. Furthermore, retrospective study usually has selection bias, which means that better survival may be in uenced by the other meaningful good characteristics including better performance status, earlier T or N stage, lesser tumor burden, which are apt to choose operation, not only disposal itself.…”
Section: Discussionmentioning
confidence: 99%
“…What's more, the quality of life (QOL) after surgery which has been proved meaningful in the evaluation of survival bene t is missed in this study due to data unavailable. [8,11,30] In addition, we only involve part of the meaningful factors, and other researches have already investigated that right colon, late TN stage, carcinoembryonic antigen (CEA) and lactate dehydrogenase (LDH) etc. are also prognostic predictor.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported on the prediction of metastatic Ewing's sarcoma(MES) models-ROC 6 . But now, nomograms were the graphical description of predictive statistical model, which has been widely used to accurately predict the survival of cancer patients, such as bladder cancer, colon and breast cancer [7][8][9][10][11] . To the best of our knowledge, nomogram have not been used in patients with metastatic ES.…”
Section: Introductionmentioning
confidence: 99%